ANALISIS PENERAPAN PENCATATAN AKUNTANSI DAN PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN SAK-EMKM PADA UMKM DI KABUPATEN SOLOK SELATAN (STUDI KASUS RIKA BAKERY & CAKE DAN RUMAH MAKAN SUNGAI KALU) - Alyani Atsarina; Romi Rianto Harapan; Windi Sasa Prima (Ensiklopedia of Journal, 2023)
This study aims to see the application of recording and preparation of financial reports based on SAK-EMKM for UMKM in South Solok district. This research is a descriptive research with a qualitative approach. Data collection techniques are interviews, questionnaires, and documentation. The technique of checking the validity of the data in this study is the triangulation technique. From the results of the study, it was found that two UMKM (Rika Bakery & Cake and Sungai Kalu Restaurant) in South Solok District had implemented accounting records and preparation of financial reports properly and correctly due to the background of financial staff who had studied in college.Keywords:UMKM, SAK EMKM, Financial Statement